Economic linkage between urban development and livelihood of peri-urban farming communities in Ethiopia (policies and practices) - Idris Mohammed; Abdella Kosa; Nuredin Juhar (Agricultural and Food Economics, 2020)
As urban expands into peripheral areas, peri-urban indigenous farmers lose their land and highly vulnerable to negative externalities of urbanization. The aim of the study is to assess the economic linkage between urban development and the livelihood of peri-urban farming communities, focus on current practice and policies. From Ethiopia, Amara regional state was selected. Through multistage sampling, five municipalities (Debra Birhan, Shewa Robit, Kombolcha, Dessie, and Woldia) were taken as the sample from Amara regional state. Interviews were conducted with 30 municipalities' officials of the selected town. Questionnaires collected from 200 respondents of peri-urban evicted farmers. As the findings of the study suggest, peri-urban farmers' evictions from their indigenous land for land re-development are the continuous process that negatively affects the livelihood of farming communities. The factors that contribute for urban expansion in Amara regional state are economic policy reform, the creation of enabling the environment for private investors, the unsatisfied demand of urban dwellers for residential, and expansion of public sector projects. A collaborative effect of policy limitations, potential conflicts, unplanned livelihood, and poor saving habits of peri-urban farmers, lack of municipality intervention and lack of good governance negatively affect the livelihood of peri-urban farmers and jeopardize the image of government. The forwarded solutions are municipalities should have fully implemented urban policies, should have work on mutual benefits of concerned stakeholders, farmers' background should be recorded and continuous follow up of evicted farmers livelihood should be practiced.
Keywords: 330; Urban expansion; Economic linkage; Attitude; Challenges